Crimean-Congo Hemorrhagic Fever A Global Perspective - Ergonul, Onder; Whitehouse, Chris A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2007)
Crimean-Congo hemorrhagic fever (CCHF) is a tick-borne disease associated with severe hemorrhagic manifestations. CCHF has been referred to as the "Asian Ebola." However, in fact, the disease is one of the most widely distributed tick-borne diseases in the world, occurring in Africa, Asia, Europe, and the Middle East. This volume covers major aspects of this important disease and the virus which causes it. Chapters are written by leading experts in their fields and detail historical, public health, epidemiological, and clinical aspects of CCHF and the genetics and molecular biology of the virus. Additional chapters focus on disease control, tick vectors and infection among animals, both natural and experimental. This book will be of interest to virologists, microbiologists, medical entomologists, infectious disease physicians, epidemiologists, public health specialists, veterinary scientists, public health policy makers, journalists, and medical educators.
and Historical Perspectives -- A Historical Perspective of Infectious Diseases with Reference to Crimean-Congo Hemorrhagic Fever -- Personal Reflections -- Etiologic Agent -- Molecular Biology of the Crimean-Congo Hemorrhagic Fever Virus -- Molecular Epidemiology, Genomics, and Phylogeny of Crimean-Congo Hemorrhagic Fever Virus -- Epidemiology and Ecology -- Crimean-Congo Hemorrhagic Fever in Turkey -- Epidemiology of Crimean-Congo Hemorrhagic Fever in the Balkans -- Crimean-Congo Hemorrhagic Fever Infection in Iran -- Crimean-Congo Hemorrhagic Fever in Russia and Other Countries of the Former Soviet Union -- Crimean-Congo Hemorrhagic Fever in the Xinjiang Uygur Autonomous Region of Western China -- Crimean-Congo Hemorrhagic Fever in South Africa -- Role of Ticks in the Transmission of Crimean-Congo Hemorrhagic Fever Virus -- Crimean-Congo Hemorrhagic Fever Virus Infection among Animals -- Ecology of Tick-Borne Disease and the Role of Climate -- Mathematical Modeling of Crimean-Congo Hemorrhagic Fever Transmission -- Clinical Features, Pathogenesis, and Treatment -- Clinical and Pathologic Features of Crimean-Congo Hemorrhagic Fever -- Comparative Pathogenesis of Crimean-Congo Hemorrhagic Fever and Ebola Hemorrhagic Fever -- Laboratory Diagnosis of Crimean-Congo Hemorrhagic Fever -- Treatment of Crimean-Congo Hemorrhagic Fever -- Prevention and Control -- Risk Groups and Control Measures for Crimean-Congo Hemorrhagic Fever -- Estimates and Prevention of Crimean-Congo Hemorrhagic Fever Risks for Health-Care Workers -- International Surveillance and Control of Crimean-Congo Hemorrhagic Fever Outbreaks -- Remaining Questions and Future Research -- Future Research.
Keywords: Virology; Bacteriology; Parasitology; Virology; Bacteriology; Parasitology